Thermal Conductivity of Glycerol at Atmospheric Pressure Between 268 K and 363 K by Using a Steady-State Parallel-Plate Instrument - Bioucas, Francisco; Koller, Thomas Manfred; Fröba, Andreas Paul (International Journal of Thermophysics, 2024)
The present work reports experimental data for the thermal conductivity of glycerol which is an important fluid in many technical applications. Measurements were performed in an absolute way at ambient pressure using a steady-state guarded parallel-plate instrument (GPPI) with an average expanded (k = 2) measurement uncertainty of 2.3%. For data representation over a temperature range from (268.15 to 363.15) K in steps of 5 K, the thermal conductivities are averaged from measurements at three different temperature gradients for each temperature. The present results indicate an almost constant thermal conductivity of glycerol over the studied temperature range and agree with the sparse experimental data available in the literature. Based on the experimental database including the results from this work, a simple correlation for the thermal conductivity of glycerol at 0.1 MPa as a function of temperature between (268 and 413) K is suggested. The additional study on the influence of water as possible contamination up to water mass fractions of 0.02 on the thermal conductivity of glycerol reveals negligible changes. Overall, the experimental results from this work contribute to an improved data situation for the thermal conductivity of glycerol, particularly in the subcooled liquid region at temperatures below 283 K.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Correlation; Glycerol; Liquid; Parallel-plate instrument; Subcooled liquid; Thermal conductivity